FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN TINGKAT PARTISIPASI ANGGOTA KOPERASI (Kasus pada KUD Tenera Jaya Di Desa Banjar Panjang Kecamatan Kerumutan Kabupaten Pelalawan dan Koperasi Bina Usaha Desa Benayah Kecamatan Pusako Kabupaten Siak Provinsi Riau) - Marliati Ahmad; Rila Afandi; Dewi Nurmala Nurmala (UIR Press, 2019)
ABSTRACT Cooperation is a profit-oriented and family-based social organization that aim to help in increasing the budget. This study aims to analyze: characteristics of management, employees, and members of the Cooperation, factors related to the level of cooperation member participation. This research was carried out at the KUD Tenera Jaya, Banjar Panjang Village, Kerumutuan District, Pelalawan Regency and Bina Usaha Cooperative in Benayah Village, Pusako District, Siak Regency, Riau Province, during 6 months. The method used in this study is a survey method. The respondents consisted of members, management and employees. Management and Employee Respondents were taken in a census, that is, 3 cooperatives and 3 employees' cooperatives. Respondents from the Tenera Jaya Cooperative were taken by cluster sampling, 44 were taken from 370 people. Samples of members of the Cooperative Business Development taken by stratified sampling are 60 people out of 210 people. Data were analyzed descriptively qualitative and quantitative descriptive approach. The results of the study were average of management age 51 years, employees of 35 years and 49.81 years. The average level of education of administrators was 10.5 years (not graduated from high school), 11.5 years employees (graduated from high school) and 8.45 years (equivalent to junior high school). The education level of management, employees, and members of the cooperation was relatively low. The average business experience of management was 10.06 years, employees were 10.33 years, and members were 12.45 years. The average amount of income from the management of palm oil was Rp 2.6 million per month, employees were Rp 2.28 million per month and members were Rp. 2.99 million per month. The average number of family management dependents was 3 people, 2 employees, and 3 members. Tenera Jaya cooperative business performance can be seen from the Value of Direct Economic Benefits and economic efficiency analysis. The level of overall participation of KUD Tenera Jaya members (participation in decision making in organizations, participation in the implementation of cooperative activities and services, participation in evaluating cooperative programs, participation in rights and obligations as members) received good category scores. The business performance of the Bina Usaha Cooperation was in a good category. The level of member participation in Bina Usaha cooperation was also a good category. Factors that significantly related to the level of farmer participation were the Cooperative Bina Usaha Performance and the experience of being a KUD member. While the other characteristic factors did not significantly relate. This means that the better the cooperative's business performance is felt by members and the more the level of member participation in the cooperative increases. In addition, the more experienced being a member of cooperation is the better the level of participation of cooperation members.